2013
DOI: 10.1159/000348450
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial on Cognitive Restructuring and Imagery Modification to Reduce the Feeling of Being Contaminated in Adult Survivors of Childhood Sexual Abuse Suffering from Posttraumatic Stress Disorder

Abstract: Background: The feeling of being contaminated (FBC) is a common phenomenon in survivors of childhood sexual abuse (CSA) suffering from posttraumatic stress disorder (PTSD). Thus far, this symptom has been neglected in research and therapy. For this reason, we developed Cognitive Restructuring and Imagery Modification (CRIM), a two-session treatment (lasting 90 and 50 min) that specifically targets the FBC. The present study examined the efficacy of the treatment. Methods: Thirty-four women with CSA-related PTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
58
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 22 publications
0
58
1
2
Order By: Relevance
“…The most recent meta-analysis on this topic (Ehring et al, 2014) included 16 randomized controlled trials (RCTs), and we identified one more (Jung & Steil, 2013). Details of these 17 studies are presented in Supplementary Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…The most recent meta-analysis on this topic (Ehring et al, 2014) included 16 randomized controlled trials (RCTs), and we identified one more (Jung & Steil, 2013). Details of these 17 studies are presented in Supplementary Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of CRIM has been tested in a randomized wait-list controlled trial of 34 victims of CSA with posttraumatic stress disorder (PTSD; Jung & Steil, 2013). The results showed a significantly greater reduction in the feeling of being contaminated among the CRIM group than among the wait-list control group.…”
Section: Introductionmentioning
confidence: 99%
“…This might indicate that a considerable proportion of patients with childhood abuse-related PTSD are lacking skills to effectively handle the emotions that are triggered by PE sessions. Second, some authors criticize that PE limits itself to the extinction of fear, and does not cover other emotions and cognitions often associated with CA-related PTSD, such as anger, irrational guilt, shame, disgust and self-contempt (Grunert, Weis, Smucker, & Christianson, 2007;Jung & Steil, 2013). Indeed, there is preliminary evidence that PE is less effective in changing trauma-related emotions of anger (Foa, Riggs, Massie, & Yarczower, 1995), guilt and shame (Arntz, Tiesema, & Kindt, 2007;Grunert et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In their protocol, ImRs was applied as an add-on to standard PE, based on the assumption that it would be ineffective to avoid exposure to the complete trauma memory. Until now, this protocol has not systematically been tested in a population with CA-related PTSD, but ImRs has been shown to improve standard exposure therapy Jung & Steil, 2013;Steil, Jung, & Stangier, 2011), and also to be effective in a sample with previous treatment failures (Grunert, Smucker, Weis, & Rusch, 2003). In addition, ImRs has been found to be effective in targeting intrusive images and memories within other disorders, such as social phobia (Wild, Hackmann, & Clark, 2007;Wild, Hackmann, & Clark, 2008), specific phobia (Hunt & Fenton, 2007), and depression (Brewin et al, 2009;Wheatly et al, 2007).…”
Section: Introductionmentioning
confidence: 99%